1967
DOI: 10.1126/science.157.3792.1077
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Hypothalamic Stimulation in Satiated Rats: The Rewarding Effects of Self-Induced Drinking

Abstract: Clearly the inactive phase cannot be explained by a general depression of the "ascending reticular system" because ECoG desynchronization (occurring either spontaneously or following stimulation of the reticular formation) was observed in cortex 1 cm or more from the site of depression. This inference is consistent with the finding of Bures et al. (18) that in the unanesthetized rat most reticular neurons only increased in rate during SD. (By contrast, the majority of medial thalamic neurons they studied showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 2 publications
3
14
0
Order By: Relevance
“…On the other hand, if Spies' [16] assumption that rewarding stimulation produces a temporary food drive reduction ("transient satiety equivalent") is accepted then it is equally puzzling that animals eat when stimulated at the brain site. Attempts to resolve the paradox by noting that different stimulation durations are typically used to evoke eating and self-stimulation are not convincing as several investigators have demonstrated both phenomena with identical parameters [2,10]. Earlier work by Margules and Olds [9] and Hoebel and Teitelbaum [8] demonstrated that self-stimulation rates in the lateral hypothalamus are potentiated by food deprivation.…”
Section: Lateral Hypothalamic Stimulationmentioning
confidence: 99%
“…On the other hand, if Spies' [16] assumption that rewarding stimulation produces a temporary food drive reduction ("transient satiety equivalent") is accepted then it is equally puzzling that animals eat when stimulated at the brain site. Attempts to resolve the paradox by noting that different stimulation durations are typically used to evoke eating and self-stimulation are not convincing as several investigators have demonstrated both phenomena with identical parameters [2,10]. Earlier work by Margules and Olds [9] and Hoebel and Teitelbaum [8] demonstrated that self-stimulation rates in the lateral hypothalamus are potentiated by food deprivation.…”
Section: Lateral Hypothalamic Stimulationmentioning
confidence: 99%
“…Unlike more naturalistic rewards, EBS does not satiate. And electrical brain stimulation at specific sites often elicits behaviors such as eating, drinking (Mendelson 1967), or copulation (Caggiula and Hoebel 1966). Many abused drugs, such as cocaine, amphetamine, heroin, cannabis, and nicotine, lower the threshold at which animals will lever-press for EBS (Wise 1996).…”
Section: Electrical Brain Stimulation (Ebs)mentioning
confidence: 99%
“… 10 This was supported by early experiments that contributed to our knowledge about mechanisms and circuits involved in these processes. Initial studies targeting the LHA in rodents 11 , 12 and felines 13 showed an increase in feeding, an effect partially attributed to the modulation of the medial forebrain bundle. 14 In contrast, recent experiments in rodents reported a reduction in weight gain following high-frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%